A new small-sized Theloderma (Anura: Rhacophoridae) from Laos - Sivongxay, Niane; Davankham, Monekham; Phimmachak, Somphouthone; Phoumixay, Keochay; Stuart, Bryan L. (Zootaxa, 2016)
A new species of the rhacophorid frog genus Theloderma is described from the forested shoreline of the Nam Lik Reservoir, Vientiane Province, Laos. The new species differs from its congeners by having the combination of males with SVL 17.0–20.6; pearly asperities on dorsum; no vomerine teeth; disc diameter of finger III ca. 40% of tympanum diameter; uniformly gray venter; light brown dorsum with darker brown and black markings; and a uniformly bronze iris with small black reticulations. Molecular phylogenetic analysis of mitochondrial DNA sequence data infers that the new species is most closely related to T. lateriticum from northern Vietnam. Evidence for the monophyly of Theloderma is reviewed.